Association between serum uric acid and metabolic syndrome components in prepubertal obese children (Tanner Stage I) from Nuevo León, Mexico - a preliminary study - Solís Pérez, Elizabeth; González Medina, Mario Alberto; López Cabanillas Lomelí, Manuel; Tijerina González, Verónica; Villarreal Pérez, Jesús Zacarías; Imrhan, Victorine; Juma, Shanil; Vijayagopal, Parakat; Boonme, Kittipong; Prasad, Chandan (2017)
Abstract Background: Metabolic syndrome (MetS) is a major risk factor for cardiovascular disease and diabetes. Previous studies in obese children demonstrating a positive association between serum uric acid (sUA) and components of MetS are confounded by lack of uniformity in age and pubertal status of children. Therefore, we have examined the role of sUA in MetS and its components in pre-pubertal children (Tanner Stage I, age ≤ 9 years). Methods: Pre-pubertal obese children (32 boys, 27 girls, age 6–9 years) were recruited from Nuevo Leon, Mexico. For comparison, an equal number of children with normal body mass index (BMI) in the same age range (22 Boys, 39 girls, age 6–9 years) were also recruited from the same community. Presence of MetS and its components was defined according to the criteria of International Diabetes Federation. Fasting blood was analyzed for lipids, glucose, insulin, and uric acid. Results: Among the obese children, sUA was positively associated with insulin resistance and hypertriglyceridemia and negatively associated with high density lipoprotein-cholesterol (HDLc). Subjects were three times more likely to have a MetS diagnosis per one unit (md/dL) difference in sUA. Of the 59 obese pre-pubertal children, 20 were classified as having MetS defined by the presence of abdominal obesity and two or more of other components described under methods. Of these, 57.1% (20/61) had sUA between 5.1 and 7.1 mg/dl. Conclusions: The findings of this study clearly indicate a positive relationship between uric acid and MetS and its components in pre-pubertal obese children with Tanner stage I and ≤9 years of age.